Rural Tourism in South Africa’s Apartheid Bantustans: An Historical View - Rogerson, Christian M.; Sixaba, Zinzi (Modern Geográfia)
Arguably, tourism studies can benefit from a stronger engagement with historical research. The aim is to contribute further to a limited historical tradition in international tourism geography scholarship. Past tourism in South Africa has attracted some attention from geographers who have demonstrated the relevance of historical research. The paper investigates the emergence of the Ciskei Bantustan (one of ten established under apartheid) as a rural tourism destination in the context of apartheid planning. In terms of the history of Bantustan economic development, the early focus was on industrial development with minimal attention devoted to tourism. A tourism economy did, however, emerge in these areas and given mounting policy attention, particularly from the 1970s and continuing into the post-1981 ‘independence’ period for Ciskei. The character of tourism development which occurred in ‘independent’ Ciskei (1981–1994) is analysed with particular attention to the growth of casino tourism which was surrounded by controversies about corruption in this rural destination.